The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1099/mic.0.000199
|View full text |Cite
|
Sign up to set email alerts
|

H-NS suppresses pilE intragenic transcription and antigenic variation in Neisseria gonorrhoeae

Abstract: Initially, pilE transcription in Neisseria gonorrhoeae appeared to be complicated, yet it was eventually simplified into a model where integration host factor activates a single 235/210 promoter. However, with the advent of high-throughput RNA sequencing, numerous small pilspecific RNAs (sense as well as antisense) have been identified at the pilE locus as well as at various pilS loci. Using a combination of in vitro transcription, site-directed mutagenesis, Northern analysis and quantitative reverse transcrip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 31 publications
0
10
0
1
Order By: Relevance
“…A possible explanation for the lack of translation is that in the construction of the pilE IHF deletion mutants, not only was the IHF binding site deleted but also other upstream DNA was removed, causing the asRNA7 gene to be absent as well (Hill et al, 1997). Consequently, without asRNA7, the loop structures would remain, with the pilE ribosome binding site still qRT-PCR analysis of WT, asRNA7 insertion mutant 6 (DasRNA7 : ermC6) and asRNA7 complements 1, 2 and 3 (DasRNA7 : ermC6:opaE : asRNA7 : kan1, 2 and 3) utilizing primer pairs specific for recA and the 5¢ end of pilE (Masters et al, 2016). The relative log difference as compared to an external RNA3 control.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…A possible explanation for the lack of translation is that in the construction of the pilE IHF deletion mutants, not only was the IHF binding site deleted but also other upstream DNA was removed, causing the asRNA7 gene to be absent as well (Hill et al, 1997). Consequently, without asRNA7, the loop structures would remain, with the pilE ribosome binding site still qRT-PCR analysis of WT, asRNA7 insertion mutant 6 (DasRNA7 : ermC6) and asRNA7 complements 1, 2 and 3 (DasRNA7 : ermC6:opaE : asRNA7 : kan1, 2 and 3) utilizing primer pairs specific for recA and the 5¢ end of pilE (Masters et al, 2016). The relative log difference as compared to an external RNA3 control.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, it was demonstrated that there exists an inverse relationship between the level of pilE sense RNA levels and antisense RNA production across the pilE gene (Masters et al, 2016). Consequently, a titration model was proposed whereby the presence of pilE antisense transcription helped determine the amount of pilE sense transcript levels.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations